Do networks do the works? Migration networks among Indian entrepreneurs in Poland and Belgium - Joanna Nestorowicz (University of Warsaw, Centre of Migration Research (CMR), 2008)
The thesis deals with the notion of migration networks. The focal point of the study is on the functioning of networks among immigrant entrepreneurs. Indian businessmen operating in Poland and Belgium are taken as an exemplification of the analyzed process. Theoretical considerations reflect upon various theories of migration, which are relevant for the study. Based on this analysis, a holistic conceptual framework is developed, which defines three areas of research: the migration decision making process, endogenous business-related factors and exogenous factors affecting business establishment. Based on these three areas an interview guide is developed further in the thesis. This guide was used as a research tool in order to carry out 30 semi-structured interviews with Indian entrepreneurs in Poland and Belgium. The thesis analyzes the findings from this study, what leads to recognizing the main determinant of network functioning among immigrant businessmen.
Keywords: 330; Soziales Netzwerk; Migranten; Entrepreneurship-Ansatz; Inder; Polen; Belgien